WITCHCRAFT FROM THE PERSPECTIVE OF ARTICLE 252 PARAGRAPH (1) OF THE 2023 CRIMINAL CODE AND ITS IMPLICATIONS FOR LEGAL CERTAINTY - Muhammad Iqbal Rifai; Chairuni Nasution; Sumarno (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The regulation of witchcraft under Article 252 paragraph (1) of the 2023 Criminal Code represents a criminal law response to a social phenomenon that continues to exist within Indonesian society. Witchcraft is often associated with supernatural practices that may generate fear, social conflict, and potential violence; therefore, the state considers it necessary to establish legal norms to regulate such practices. This study aims to analyze the juridical basis of the article, the elements of the criminal offense as formulated, and its implications for legal certainty and law enforcement practices. The method employed is normative legal research using statutory and conceptual approaches through a literature review. The results indicate that the criminalization of witchcraft in the new Criminal Code does not focus on proving the existence of supernatural powers, but rather on the act of a person who declares or offers services by claiming supernatural abilities that may cause suffering, illness, or death. This formulation categorizes Article 252 as a formal offense, thereby directing proof toward the perpetrator’s observable actions. This regulation is intended to protect society from fraud, psychological manipulation, and social conflict. However, the norm still has the potential to create multiple interpretations if not accompanied by clear interpretative guidelines, particularly in distinguishing between personal beliefs and criminal acts.